Exogenous organic matter and clay mineral additions regulate microbial-mineral mediated soil organic carbon accumulation in alkaline-calcareous soils - Xi Yang; Donghao Ma; Lin Chen; Ting Yang; Yongqi Zhang; Hongwei Jiang; Nan Zhang; Hongtao Zou; Congzhi Zhang; Guixiang Zhou; Yanfang Zhou; Yu Luo; et al. (Applied Soil Ecology, 2026)

Relative Contribution and Spatial Heterogeneity of Logging and Wildfires as Drivers of Carbon Loss in Subtropical Forests, China - Weiwei Jiang; Xiaocheng Zhou; Guoshuai Tian; Hao Wu; Fanglin Tan; Ruijiao Wu (Journal of the Indian Society of Remote Sensing, 2026)

BGFFNet: a semantic boundary-guided feature fusion network for cultivated land extraction from high-resolution remote-sensing images - Like Zhao; Yuqing Liu; Huanhuan Fang; Chuang Xiao; Huawei Jiang; Zhen Yang (International Journal of Remote Sensing, 2026)

Identification and complete genome sequence of a novel secovirus infecting Broussonetia kaempferi in China - Jinhong Yang; Jun Ling; Wei Jiang; Weiqing Kong (Archives of Virology, 2026)

Assessing seawater metal pollution using oyster shells as archives: Trace element variations along an intertidal reef profile - Ruiliang Fan; Yuange Chen; Qiang Cao; Longling Ouyang; Nannan Li; Wei Jiang; Nian Wei; Jiafeng Fang; Weimin Quan (Marine Pollution Bulletin, 2026)

Integrated lipidomics and transcriptomics reveal phosphatidic acid and mTOR signaling signatures of egg quality in giant grouper and brown-marbled grouper - Zhengfang Chen; Gaowei Jiang; Zilin Zhao; Hehe Du; Mudan He; Houpeng Wang; Yang Yang; Zhennian Chen; Guanghou Shui; Ding Ye; Yonghua Sun (Aquaculture, 2026)

Genetic improvement of oysters: Current status, challenges, and prospects - Kunyin Jiang; Chen Chen; Gaowei Jiang; Yong Chi; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Reviews in Aquaculture, 2024)
Oysters are one of the most commercially important shellfish species and have been cultured for thousands of years. Oyster aquaculture supports the major aquaculture industries in many countries. Over the last few decades, the oyster breeding and aquaculture industries have developed rapidly to meet the continually growing demand. Many researchers have made significant efforts toward the genetic improvement of commercially important traits in oysters. Some strains with fast‐growing, disease‐resistant, and stable shell‐colours have been developed through selective breeding. Some hybrid varieties have been developed by crossing different geographical populations or cultivated strains. Several hybrids exhibit considerable genetic variation and improved productive performance. Additionally, polyploid induction technologies have been applied in the oyster aquaculture industry, which provides a useful tool for performance improvement and genetic containment of cultured stocks. At present, the development of molecular breeding also provides a great opportunity for oyster genetic improvement. These advances in oyster breeding have improved the quality of oysters, brought great economic benefits, and been conducive to the sustainability of oyster production. Nonetheless, there are still some limitations and obstacles in oyster breeding, such as infectious diseases, summer mortality, conservation of germplasm resources, environmental contamination, and climate change. The present review provides an overview of the current status, challenges, and prospects in oyster breeding.

Effects of UV-C radiation on the survival of copepods and oocysts: implications for drinking water processing facilities - Chen Gong; Antai Wang; Huirong Chen; Wei Jiang; Lin Tan; Zhangli Hu (Hydrobiologia, 2013)